Catalyst as well as preparation method and application thereof

The Ru@P-CN catalyst, prepared via phosphorus doping and Ru loading, addresses the issues of low activity and stability in HER catalysts, demonstrating superior performance in both acidic and alkaline conditions.

CN119144994APending Publication Date: 2024-12-17KUNMING UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411084704.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing catalysts for hydrogen evolution reaction (HER) in water electrolysis suffer from low catalytic activity and poor stability, particularly in alkaline and acidic environments, limiting their industrial application due to issues like agglomeration, dissolution, and high cost.

Method used

A catalyst comprising a P-doped CN material with ruthenium (Ru) nanoparticles loaded on its surface (Ru@P-CN) is prepared through a method involving phosphorus doping and subsequent freeze-drying and annealing, enhancing electron transfer and adsorption of reaction intermediates.

Benefits of technology

The Ru@P-CN catalyst exhibits high catalytic activity and stability in both acidic and alkaline environments, with improved charge transfer and reduced agglomeration, outperforming commercial Pt/C catalysts in hydrogen evolution performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144994A_ABST
    Figure CN119144994A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst and a preparation method and application thereof, and the catalyst comprises a P-doped CN material and Ru loaded on the surface of the P-doped CN material, and is recorded as a Ru-P-CN catalyst. The catalyst provided by the invention shows good catalytic activity and stability in both an acid environment and an alkaline environment through doping regulation and control of phosphorus and in combination with the loaded ruthenium nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy catalysis technology, and in particular to a catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen energy is a secondary energy source with abundant sources, green and low carbon, and wide application. It is of great significance to build a clean, low-carbon, safe and efficient energy system. Among many hydrogen production technologies, water electrolysis is an ideal method for sustainable and low-pollution preparation of clean energy hydrogen. Electrocatalytic decomposition of water through hydrogen evolution reaction (HER) is an important process for efficient conversion of hydrogen. Because it produces oxygen and hydrogen by electrolysis of water, the raw material only needs water without various polluting elements, and the preparation process does not produce carbon-containing byproducts. Oxygen as the only byproduct is beneficial to the reduction of the greenhouse effect. Therefore, the water electrolysis hydrogen production technology is highly consistent with my country's current green, clean and sustainable development strategy. At the same time, the prepared hydrogen can be further converted into electrical energy and incorporated into the power system for use by power consumption systems at all levels, thereby optimizing the energy system, improving utilization efficiency, and facilitating the solution of new energy consumption problems, thereby stabilizing the security of the national power grid. The equipment used in water electrolysis technology is relatively simple and the technology is mature. The hydrogen production process is pollution-free, but it has disadvantages such as relatively high cost, high energy consumption, and low efficiency, which limits further large-scale expansion. Theoretically, the thermodynamic potential of electrocatalytic water splitting is 1.23V. However, in the actual reaction process, due to the emergence of problems such as electrode polarization, stability and overpotential deviation, more energy consumption is often generated. Therefore, in order to achieve large-scale application of electrolytic water splitting, it is very necessary to design catalysts with high activity and sufficient stability. As a key component of electrochemical water splitting technology, electrocatalysts determine the energy conversion efficiency of hydrogen evolution reaction (HER). Therefore, the energy market urgently needs efficient and stable catalysts with low overpotential to achieve large-scale application and industrialization.

[0003] At present, catalysts prepared from platinum group metals have shown good comprehensive performance, among which Pt-based catalysts have shown good HER catalytic activity. However, the high price of Pt, poor stability in alkaline environments, and high carrier costs have hindered its industrial development.

[0004] Suitable catalyst carriers can further improve the stability and corrosion resistance of the catalyst during the catalytic reaction. Some carriers can also prevent agglomeration and provide more active sites for the catalyst. For example, the commonly used Pt-based catalyst uses activated carbon as a carrier to show relatively excellent catalytic performance and stability, and related products have also been widely used commercially. In recent years, composite catalysts have also been prepared using new materials such as MOF (metal-organic framework materials), carbon nanotubes, and metal nitrides as carriers. However, the cost of these carrier materials is relatively high, and the carriers are prone to corrosion under acidic and other environmental conditions, causing the agglomeration, dissolution, migration, and shedding of the catalyst, which to a certain extent affects the service life of the catalyst and reduces the actual application value of the catalyst.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a catalyst and a preparation method and application thereof, so as to solve the problems of low catalytic activity and poor stability of the existing catalysts.

[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0008] In a first aspect of the present invention, a catalyst is provided, comprising a P-doped CN material and Ru loaded on the surface of the P-doped CN material, denoted as Ru@P-CN catalyst.

[0009] Preferably, the mass content of Ru in the catalyst is 10-15%.

[0010] The second aspect of the present invention provides a method for preparing the above catalyst, the preparation method comprising the following steps:

[0011] The phosphorus source and the nitrogen-rich precursor are dissolved in water, stirred, and evaporated to obtain a white product;

[0012] Under inert gas conditions, the white product is sintered to obtain a P-doped CN material, which is denoted as P-CN;

[0013] The P-CN is placed in a ruthenium source solution, and freeze-dried and annealed in sequence to obtain the Ru@P-CN catalyst.

[0014] Preferably, the molar ratio of the phosphorus source to the nitrogen-rich precursor is 1:(5-10).

[0015] Preferably, the phosphorus source is selected from one of hydroxyethylidene diphosphonic acid, hydroxyethylidene diphosphonic acid, and methylene diphosphonic acid, the nitrogen-rich precursor is selected from one of dicyandiamide, urea, melamine, and thiourea, and the ruthenium source is selected from ruthenium chloride or ruthenium acetylacetonate.

[0016] Preferably, the sintering step is specifically as follows: heating the temperature to 450-550°C at a heating rate of 2.5-7.5°C / min, and keeping the temperature at 450-550°C for 3 hours.

[0017] Preferably, the flow rate of the inert gas is 100-300 mL / min.

[0018] Preferably, the freeze-drying step is specifically as follows: freezing at -30 to -20°C for 10 to 14 hours, and then vacuum drying at -55 to -40°C for 20 to 28 hours.

[0019] Preferably, the annealing step is specifically as follows: heating to 350-450° C. at a heating rate of 2-5° C. / min, and keeping the temperature at 350-450° C. for 1-2 hours.

[0020] The third aspect of the present invention provides use of the above catalyst or the catalyst prepared by the above preparation method in hydrogen evolution by electrolysis of water.

[0021] Beneficial effects:

[0022] The present invention discloses a catalyst and a preparation method and application thereof. Through phosphorus doping regulation and combination with loaded ruthenium nanoparticles, the prepared catalyst exhibits good catalytic activity and stability in both acidic and alkaline environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a transmission electron microscopy image of Ru@P-CN prepared in Example 1 of the present invention.

[0024] Figure 2 X-ray diffraction patterns of g-C3N4, P-CN, Ru@g-C3N4, and Ru@P-CN prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1, respectively.

[0025] Figure 3 FT-IR Fourier infrared spectra of g-C3N4, P-CN, Ru@g-C3N4, and Ru@P-CN prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 of the present invention, respectively.

[0026] Figure 4These are the hydrogen evolution performance diagrams and Tafel curves of g-C3N4, P-CN, Ru@g-C3N4, and Ru@P-CN prepared respectively in 1 M KOH alkaline environment according to Comparative Example 1, Comparative Example 2, Comparative Example 3 of the present invention and Example 2.

[0027] Figure 5 The hydrogen evolution performance diagram and Tafel curve diagram of g-C3N4, P-CN, Ru@g-C3N4, and Ru@P-CN prepared in comparative examples 1, 2, 3, and example 2 of the present invention, respectively, under an acidic environment of 0.5M H2SO4.

[0028] Figure 6 The Ru@P-CN catalyst prepared in Example 2 of the present invention under alkaline and acidic conditions at 100 mA cm -2 Stability test curve under current density. DETAILED DESCRIPTION

[0029] The present invention provides a catalyst and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0030] An embodiment of the present invention provides a catalyst, which includes a P-doped CN material and Ru loaded on the surface of the P-doped CN material, and is denoted as a Ru@P-CN catalyst.

[0031] In this embodiment, the doped P replaces the carbon on the 3-s-triazine ring of the CN material to form a PN bond, and a carrier P-CN is obtained. P and N both play the role of anchoring Ru, and can form Ru-N and Ru-P bonds with Ru. The coordination of Ru-N and Ru-P is beneficial to electron transfer and the adsorption of reaction intermediates, and there is a strong interaction between the carrier P-CN and Ru. Therefore, the catalyst provided by the embodiment of the present invention has excellent catalytic stability, rapid charge transfer ability and faster kinetics.

[0032] Moreover, since the 3-s-triazine ring, i.e., the graphite-like phase structure, has good stability, the P doping replaces the position of carbon in the structure and maintains the original graphite-like phase structure to a certain extent, thereby ensuring the stability of the CN material. In addition, the P doping improves the conductivity of the CN material, which is beneficial to mass transfer and charge transfer.

[0033] In addition, due to the efficient coupling of Ru-N and Ru-P, the high utilization of catalytic sites, the excellent conductivity of carbon nanosheets, and the strong interaction between Ru and P-CN nanosheets, the catalyst provided by the embodiment of the present invention has a high HER catalytic activity.

[0034] In some embodiments, in the Ru@P-CN catalyst, the mass content of Ru in the catalyst is 10-15%.

[0035] If the dosage of ruthenium is too low, the amount of active substances will be reduced, resulting in poor catalytic effect. If the dosage is too high, the catalytic effect may be affected due to agglomeration, and the economic efficiency will decrease.

[0036] The present invention provides a method for preparing the above catalyst, which comprises the following steps:

[0037] The phosphorus source and the nitrogen-rich precursor are dissolved in water, stirred, and evaporated to obtain a white product;

[0038] Under inert gas conditions, the white product is sintered to obtain a P-doped CN material, which is denoted as P-CN;

[0039] The P-CN is placed in a ruthenium source solution, and freeze-dried and annealed in sequence to obtain the Ru@P-CN catalyst.

[0040] In some embodiments, the molar ratio of the phosphorus source to the nitrogen-rich precursor is 1:(5-10).

[0041] In some embodiments, the phosphorus source is selected from one of hydroxyethylidene diphosphonic acid, hydroxyethylidene diphosphonic acid, and methylene diphosphonic acid, the nitrogen-rich precursor is selected from one of dicyandiamide, urea, melamine, and thiourea, and the ruthenium source is selected from ruthenium chloride or ruthenium acetylacetonate, but is not limited to this. Other substances that can be used as phosphorus sources, nitrogen-rich precursors, and ruthenium sources are also within the scope of the present invention.

[0042] There is an acid-base interaction between the phosphorus source (hydroxyethylidene diphosphonic acid as an example) and the nitrogen-rich precursor (melamine as an example) to promote crosslinking. The following structure is a P-CN doping substitution model. P may replace the angular carbon or bay carbon in the structure, and then sintering treatment is carried out under inert gas, resulting in decomposition and polymerization to finally obtain the P-doped CN material P-CN.

[0043]

[0044] Specifically, the participation of the heteroatom part (i.e., diphosphonic acid) can strongly interact with melamine on the basis of the acid-base crosslinking effect, thereby changing the polymerization mode in situ during the sintering process. The high thermal stability of the phosphorus source (over 500°C) ensures a large amount of uniform doping of P. P-CN still maintains a high stability at around 500°C, which is almost equivalent to g-C3N4 synthesized without an organic phosphorus source. At the same time, the doping of P atoms and the remaining motif can disrupt the structure of carbon nitride. The delamination effect caused by doping is conducive to the cohesion of the carbon nitride layer in the nanostructured domain, thereby reducing the surface tension. This may be due to the self-assembly effect caused by the change in the pyrolysis process. The prepared P-CN has a good nanosheet structure and stability, which is conducive to the loading of ruthenium nanoparticles.

[0045] This embodiment uses a combination of freeze drying and annealing treatment, so that there is a strong electronic interaction between N, P and Ru on the P-CN carrier, thereby achieving the effect of anchoring ruthenium nanoparticles. At the same time, the coordination of Ru-N and Ru-P is conducive to electron transfer and adsorption of reaction intermediates. Therefore, the catalyst system provided by the embodiment of the present invention has excellent catalytic stability, rapid charge transfer and faster kinetics.

[0046] In some embodiments, the molar ratio of the phosphorus source to the nitrogen-rich precursor is 1:(5-10). The molar ratio of the phosphorus source (for example, hydroxyethylidene diphosphonic acid) to the nitrogen-rich precursor (for example, melamine) can be 1:5, 1:7, 1:10. When the molar ratio is 1:7 and 1:10, good performance is also shown, but slightly weaker than 1:5.

[0047] In some preferred embodiments, the molar ratio of the phosphorus source to the nitrogen-rich precursor is 1:5.

[0048] In some embodiments, the sintering step is specifically as follows: heating to 450-550° C. at a heating rate of 2.5-7.5° C. / min, and keeping the temperature at 450-550° C. for 3 hours.

[0049] The firing temperature should be controlled between 450℃ and 550℃. Exceeding this range will lead to a decrease in material stability, and below this range the material cannot be fired successfully. The optimal temperature is 500℃, and the heating rate should be within the range of 2.5℃ to 7.5℃ / min. Too fast or too slow will affect the material morphology. The optimal temperature is 5℃.

[0050] In some preferred embodiments, the sintering step is specifically as follows: heating to 500° C. at a heating rate of 5° C. / min, and keeping the temperature at 500° C. for 3 hours.

[0051] In some embodiments, the flow rate of the inert gas is 100-300 mL / min.

[0052] In some embodiments, the mixture is frozen at -30 to -20°C for 10 to 14 hours and then vacuum dried at -55 to -40°C for 20 to 28 hours.

[0053] Freeze drying can maintain the original morphology and structure of the material as much as possible. The freezing temperature can be below -10°C. There is no strict requirement for the freezing temperature. In principle, as long as the slurry is frozen into a solid state without liquid, it can also be frozen by liquid nitrogen freezing and other methods. In short, the lower the temperature, the faster the freezing, the better.

[0054] In some preferred embodiments, the freeze-drying step is specifically: freezing at -25°C for 12 hours, and then vacuum drying at -55°C for 24 hours.

[0055] In some embodiments, the annealing step is specifically as follows: heating to 350°C to 450°C at a heating rate of 2 to 5°C / min, and keeping the temperature at 350°C to 450°C for 1 to 2 hours.

[0056] The heating rate of annealing should not be too fast, less than 5℃ / min. Too fast heating rate will lead to incomplete sintering process. It is better to control the sintering temperature in the range of 350-450℃. Too high temperature will reduce the stability of the material and destroy part of the structure of the material during the annealing of the loaded metal. The holding time is better for 1-2h. The cooling rate during annealing should not be too fast. The appropriate cooling rate (about 1-2℃ / min) can refine the metal particles.

[0057] In some preferred embodiments, the annealing step is specifically as follows: heating to 400° C. at a heating rate of 2.5° C. / min, and keeping the temperature at 400° C. for 90 min.

[0058] The embodiment of the present invention also provides the use of the above catalyst in hydrogen evolution by electrolysis of water.

[0059] In some embodiments, the method for preparing the catalyst comprises the following steps:

[0060] Preparation of the carrier: hydroxyethylidene diphosphonic acid (C2H8O7P2) is used as a phosphorus source and mixed with melamine (C3H6N6) in a certain proportion, and then stirred, evaporated, dried, and the product is collected and ground for the first time. The ground product is placed in a crucible and sintered once in a tubular furnace under a nitrogen atmosphere to obtain a reddish-brown carrier. Alcohol is added for a second grinding to obtain a reddish-brown powder, which is recorded as P-CN.

[0061] Catalyst synthesis: Add RuCl3 aqueous solution to a beaker, disperse the prepared P-CN in the RuCl3 solution, stir and ultrasonically vibrate to obtain a mixed slurry, then pour the mixed slurry into a petri dish and seal it with plastic wrap, then freeze-dry to obtain a dark brown precursor, grind the precursor thoroughly and place it in a crucible, and anneal it in a tube furnace. The whole process is carried out under N2 atmosphere to obtain Ru@P-CN.

[0062] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are only for illustrating the present invention but not limiting the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0063] Example 1

[0064] The preparation of the catalyst comprises the following steps:

[0065] Weigh 0.5 g of melamine and 0.1776 g of hydroxyethylidene diphosphonic acid and add them to 15 mL of deionized water. Stir and evaporate at 50 ° C and 600 r / min until dry. Then take out the white product and grind it for the first time for 1 min. Then add it to a crucible and sinter it in nitrogen with a nitrogen flow rate of 100 mL / min. Pre-ventilate for 20 min, heat it to 500 ° C at a rate of 5 ° C / min, keep it at 500 ° C for 3 h, cool it to room temperature, take it out, add 5 mL of alcohol to the obtained material and grind it for the second time. After grinding for 10 min, a reddish-brown powder is obtained, which is recorded as P-CN.

[0066] Add 5mL of RuCl3 aqueous solution with a concentration of 2mg / mL to a beaker, disperse 52.5mg of P-CN in 5mL of RuCl3 solution, stir for 10min and then ultrasonically vibrate for 10min to obtain a mixed slurry, then pour the mixed slurry into a culture dish, seal it with plastic wrap, freeze it at -25℃ for 10h, and then freeze-dry it in a freeze dryer at -55℃ and vacuum conditions for 20h to obtain a dark brown precursor and dry grind it for 5min. Put the ground precursor into a crucible and anneal it in a tubular furnace under a nitrogen atmosphere with a nitrogen flow rate of 100mL / min, pre-ventilate for 20min, and heat it to 400℃ at a rate of 2.5℃ / min. Keep it at 400℃ for 90min, cool it to room temperature and take it out to obtain the catalyst Ru@P-CN.

[0067] Example 2

[0068] The preparation of the catalyst comprises the following steps:

[0069] Weigh 1 g of melamine and 0.3552 g of hydroxyethylidene diphosphonic acid and add them to 30 mL of deionized water. Stir and evaporate at 60 ° C and 800 r / min until dry. Then take out the white product and grind it for the first time for 2 minutes. Then add it to a crucible and sinter it in nitrogen with a nitrogen flow rate of 200 mL / min. Pre-ventilate for 25 minutes, heat it to 500 ° C at a rate of 5 ° C / min, keep it at 500 ° C for 3 hours, cool it to room temperature, take it out, add 7.5 mL of alcohol to the obtained material and grind it for the second time. After grinding for 15 minutes, a reddish-brown powder is obtained, which is recorded as P-CN.

[0070] Add 10mL of RuCl3 aqueous solution with a concentration of 2mg / mL into a beaker, disperse 105mg of P-CN in 10mL of RuCl3 solution, stir for 15min and then ultrasonically vibrate for 15min to obtain a mixed slurry, then pour the mixed slurry into a culture dish, seal it with plastic wrap, freeze it at -25℃ for 12h, and then freeze-dry it in a freeze dryer at -55℃ under vacuum for 24h to obtain a dark brown precursor and dry grind it for 10min. Put the ground precursor into a crucible and anneal it in a tubular furnace under a nitrogen atmosphere with a nitrogen flow rate of 200mL / min, pre-ventilate for 25min, and heat it to 400℃ at a heating rate of 2.5℃ / min. Keep it at 400℃ for 90min, cool it to room temperature and take it out to obtain the catalyst Ru@P-CN.

[0071] Example 3

[0072] The preparation of the catalyst comprises the following steps:

[0073] Weigh 2 g of melamine and 0.7104 g of hydroxyethylidene diphosphonic acid and add them to 45 mL of deionized water. Stir and evaporate at 70 ° C and 1000 r / min until dry. Then take out the white product and grind it for the first time for 3 minutes. Then add it to a crucible and sinter it in nitrogen with a nitrogen flow rate of 300 mL / min. Pre-ventilate for 30 minutes, heat it to 500 ° C at a rate of 5 ° C / min, keep it warm at 500 ° C for 3 hours, cool it to room temperature, take it out, add 10 mL of alcohol to the obtained material and grind it for the second time. After grinding for 20 minutes, a reddish-brown powder is obtained, which is recorded as P-CN.

[0074] Add 20mL of RuCl3 aqueous solution with a concentration of 2mg / mL into a beaker, disperse 210mg of P-CN in 20mL of RuCl3 solution, stir for 20min and then ultrasonically vibrate for 20min to obtain a mixed slurry, then pour the mixed slurry into a culture dish, seal it with plastic wrap, freeze it at -25℃ for 14h, and then freeze-dry it in a freeze dryer at -55℃ under vacuum for 28h to obtain a dark brown precursor and dry grind it for 15min. Put the ground precursor into a crucible and anneal it in a tubular furnace under a nitrogen atmosphere with a nitrogen flow rate of 200mL / min, pre-ventilate for 30min, and heat it to 400℃ at a rate of 2.5℃ / min. Keep it at 400℃ for 90min, cool it to room temperature and take it out to obtain the catalyst Ru@P-CN.

[0075] Comparative Example 1

[0076] A catalyst preparation method includes the following steps: adding 1 g of melamine into a crucible and calcining in a tube furnace. The whole process is carried out under a nitrogen atmosphere with a flow rate of 200 mL / min and a heating rate of 5 °C min -1 , kept at 500℃ for 3h, then ground it, added 7.5mL of alcohol to the obtained material and ground it, and after grinding for 15min, a light yellow powder was obtained, which was recorded as g-C3N4.

[0077] Comparative Example 2

[0078] The invention discloses a catalyst preparation method, comprising the following steps: adding 30 mL of deionized water into a beaker, adding 1 g of melamine and 0.3552 g of hydroxyethylidene diphosphonic acid thereto, stirring and evaporating at 60°C and 800 r / min until dry, taking out a white product, grinding it for the first time for 2 minutes, adding it into a crucible, sintering it in nitrogen with a nitrogen flow rate of 200 mL / min, pre-ventilating for 25 minutes, heating it to 500°C at a rate of 5°C / min, keeping it warm at 500°C for 3 hours, taking it out after cooling it to room temperature, adding 7.5 mL of alcohol into the obtained material, grinding it for the second time, grinding it for 15 minutes to obtain a reddish brown powder, which is recorded as P-CN.

[0079] Comparative Example 3

[0080] A preparation method of a catalyst comprises the following steps:

[0081] 1 g of melamine was added into the crucible and calcined in a tube furnace. The whole process was carried out under nitrogen atmosphere with a flow rate of 200 mL / min and a heating rate of 5 °C min -1, kept at 500℃ for 3h, then ground it, added 7.5mL of alcohol to the obtained material and ground it, and after grinding for 15min, a light yellow powder was obtained, which was recorded as g-C3N4.

[0082] Add 10mL of RuCl3 aqueous solution with a concentration of 2mg / mL into a beaker, disperse 105mg of the g-C3N4 prepared above in 10mL of RuCl3 solution, stir for 15min and then ultrasonically vibrate for 15min, then pour the mixed slurry into a culture dish, seal it with plastic wrap, freeze it at -25℃ for 12h, then freeze-dry it in a freeze dryer at -55℃ and vacuum for 24h to obtain a color precursor and dry grind it for 10min, put the ground precursor into a crucible, and anneal it in a tubular furnace under a nitrogen atmosphere with a nitrogen flow rate of 200mL / min, pre-ventilate for 25min, and heat it to 400℃ at a rate of 2.5℃ / min, keep it at 400℃ for 90min, cool it to room temperature and take it out to obtain the catalyst Ru@g-C3N4.

[0083] The performance of the catalysts prepared in Example 2 and Comparative Examples 1-3 was characterized as follows:

[0084] like Figure 1 As shown, the prepared Ru@P-CN catalyst retains the nanosheet structure of the graphite phase carbon nitride material, the ruthenium nanoparticles are small in size and evenly dispersed on the surface of the nanosheets, and the modified carbon nitride material effectively inhibits the agglomeration of ruthenium nanoparticles during loading.

[0085] Figure 2 The X-ray diffraction patterns of g-C3N4, P-CN, Ru@g-C3N4, and Ru@P-CN prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, and Example 2, respectively, show that the modified CN material carrier and the catalyst loaded with ruthenium have better maintained the characteristic peaks of the carbon nitride material, and the characteristic peaks of ruthenium correspond one to one. The peaks tend to shift to small angles, and the intensity of the characteristic peaks is weakened. This is because the doped phosphorus replaces part of the carbon position in the original structure of the CN material, which is beneficial to improve the activity and stability of the catalyst.

[0086] Figure 3 FT-IR Fourier transform infrared spectra of g-C3N4, P-CN, Ru@g-C3N4, and Ru@P-CN prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, and Example 2, respectively. From the structures shown in the figure, it can be seen that the carrier material prepared in Comparative Example 2 and the catalyst material prepared in Example 2 retain the graphite-like phase structure, which ensures that the catalyst has good stability.

[0087] Figure 4The hydrogen evolution performance graphs and Tafel curves of g-C3N4, P-CN, Ru@g-C3N4, and Ru@P-CN prepared in alkaline environment respectively in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 2 are shown. It can be seen that the Ru@P-CN prepared in Example 2 exhibits good catalytic activity in the test catalyst in 1M KOH, and its catalytic performance is better than that of commercial Pt / C.

[0088] Figure 5 The hydrogen evolution performance graphs and Tafel curves of g-C3N4, P-CN, Ru@g-C3N4, and Ru@P-CN prepared in acidic environment respectively in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 2 are shown. It can be seen that the Ru@P-CN prepared in Example 2 exhibits good catalytic activity in the test catalyst in 0.5M H2SO4, and its catalytic performance is close to that of commercial Pt / C.

[0089] Figure 6 The stability test curve of Ru@P-CN prepared in Example 2 under alkaline and acidic environments is shown in Figure 2. -2 Under the 36h long-term stability test at current density, the Ru@P-CN catalyst prepared by the present invention exhibited good catalytic stability.

[0090] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A catalyst, characterized in that The catalyst includes a P-doped CN material and Ru loaded on the surface of the P-doped CN material, which is denoted as a Ru@P-CN catalyst.

2. The catalyst according to claim 1, characterized in that In the Ru@P-CN catalyst, the mass content of Ru in the catalyst is 10-15%.

3. A method for preparing the catalyst according to any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: The phosphorus source and the nitrogen-rich precursor are dissolved in water, stirred, and evaporated to obtain a white product; Under inert gas conditions, the white product is sintered to obtain a P-doped CN material, which is denoted as P-CN; The P-CN is placed in a ruthenium source solution, and freeze-dried and annealed in sequence to obtain the Ru@P-CN catalyst.

4. The method for preparing the catalyst according to claim 3, characterized in that: The molar ratio of the phosphorus source to the nitrogen-rich precursor is 1:(5-10).

5. The method for preparing the catalyst according to claim 3, characterized in that: The phosphorus source is selected from one of hydroxyethylidene diphosphonic acid, hydroxyethylidene diphosphonic acid, and methylene diphosphonic acid; the nitrogen-rich precursor is selected from one of dicyandiamide, urea, melamine, and thiourea; and the ruthenium source is selected from ruthenium chloride or ruthenium acetylacetonate.

6. The method for preparing the catalyst according to claim 3, characterized in that: The sintering treatment step specifically comprises: heating the temperature to 450° C. to 550° C. at a heating rate of 2.5 to 7.5° C. / min, and keeping the temperature at 450° C. to 550° C. for 3 hours.

7. The method for preparing the catalyst according to claim 3, characterized in that: The flow rate of the inert gas is 100-300 mL / min.

8. The method for preparing a catalyst according to claim 3, characterized in that: The freeze-drying treatment steps are specifically: freezing at -30 to -20°C for 10 to 14 hours, and then vacuum drying at -55 to -40°C for 20 to 28 hours.

9. The method for preparing a catalyst according to claim 3, characterized in that: The annealing treatment step specifically comprises: heating to 350-450° C. at a heating rate of 2-5° C. / min, and keeping the temperature at 350-450° C. for 1-2 hours.

10. Use of the catalyst according to any one of claims 1 to 2 or the catalyst prepared by the preparation method according to any one of claims 3 to 9 in hydrogen evolution by electrolysis of water.